Advancements in Automotive Braking Technology for Enhanced Safety: A Review - Agus Lutanto; Aprianur Fajri; Kacuk Cikal Nugroho; Fajrul Falah (Multidisciplinary Innovations and Research in Applied Engineering, 2024)
This research explores advancements in braking technology with a focus on enhancing vehicle safety. The topic was chosen due to the critical importance of literature connecting braking technology developments to safety levels. The method employed was a comprehensive review of current literature concerning types and advancements in braking technologies, particularly in automotive vehicles. Analysis indicates that integrating modern braking technologies can significantly enhance driving safety and comfort, although challenges related to costs and maintenance need further attention. Further studies are recommended to optimize the future implementation of these technologies.